Growth of Carbon Nanotubes on Carbon/Cobalt Films with Different sp2/sp3 Ratios. (25th June 2013) - Xu, Naiyun; Tsang, Siu Hong; Tay, Beng Kang; Teo, Edwin Hang Tong; Ng, Chee Mang
Abstract : The need of barrier layer such as SiO2 for carbon nanotubes (CNTs) growth limits their performance in electronic applications. In this study, conductive carbon/metal (carbon/cobalt—C:Co) composite films with the same metal content, but different sp 2 /sp 3 ratios, were deposited using dual-source filtered cathodic vacuum arc (FCVA) technique. Three different C:Co composite films were deposited at different temperatures; visible Raman spectroscopy indicates that the sp 2 -rich C:Co composite film forms at high temperature (500°C), and high-resolution transmission electron microscopy (HRTEM) shows the formation of conducting graphitic-like sp 2 clusters and with Co nanoclusters embedded within them. Electrical measurement shows a significant decrease in film resistivity as sp 2 /sp 3 ratio increases. CNTs were successfully grown on the composite films by plasma-enhanced vapor deposition (PECVD) approach. Scanning electron microscopy (SEM) shows minor effect on the density of CNTs by varying the sp 2 /sp 3 ratio. The dependence of defect level of the as-grown CNTs is found to reduce as sp 2 /sp 3 ratio increases.